2013
DOI: 10.1007/s10008-013-2206-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of simonkolleite microplatelets on nickel foam-graphene for electrochemical supercapacitors

Abstract: Nickel foam-graphene (NF-G) was synthesised by chemical vapour deposition (CVD) followed by facial in situ aqueous chemical growth of simonkolleite (Zn 5 (OH) 8 Cl 2 ·H 2 O) under hydrothermal conditions to form NF-G/simonkolleite composite. X-ray diffraction and Raman spectroscopy show the presence of simonkolleite on the NF-G, while scanning electron and transmission electron microscopies show simonkolleite micro-plates like structure evenly distributed on the NF-G. Electrochemical measurements of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 44 publications
(41 reference statements)
5
31
0
Order By: Relevance
“…The SEM micrographs in Figure 4 clearly show the typical morphologies of the Ni substrate, under the same conditions exhibited low-intensity current peaks around 0.1 V due to the interaction of Li with graphene [35], and also to the quasi-super hydrophobicity which is attributed to poor surface wetting and thus the reduced accessibility and utilisation of the available surface area [41]. can be attributed to the presence of graphene [45].…”
Section: Morphological Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…The SEM micrographs in Figure 4 clearly show the typical morphologies of the Ni substrate, under the same conditions exhibited low-intensity current peaks around 0.1 V due to the interaction of Li with graphene [35], and also to the quasi-super hydrophobicity which is attributed to poor surface wetting and thus the reduced accessibility and utilisation of the available surface area [41]. can be attributed to the presence of graphene [45].…”
Section: Morphological Analysismentioning
confidence: 93%
“…corresponding to the characteristic G and 2D bands of graphene [41]. The D band (usually at ≈ 1350 cm -1 ), which is attributed to the disordered graphitic carbon and its intensity, provides information about the density of defects in the as-grown graphene.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…In the past few years, many studies have focused on combining graphene with metal oxides or hydroxides [9,[12][13][14][15][16], conducting polymers [12,[17][18][19], and other activated carbon materials [20,21]. Among the conducting polymers, polyaniline (PANI) and poly (3-hexylthiophene) (P3HT), which have the characteristic property of donating electrons, have recently been used in SC applications [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This is an enhancement of 3.5 times for the NF-G current collector and is a great improvement over similar studies on NiAl DHM prepared by a solvothermal technique reported elsewhere. 29 We therefore propose that the improvement in supercapacitance value is a result of the addition of a graphene layer to form the NF-G current collector which provides an improved electron transfer rate and better structural support for the DHM material 26,30 and could also ensure the retention of the capacitance even after long cycling.…”
Section: B Electrochemical Performancementioning
confidence: 99%
“…[25][26][27][28] In recent studies, Khamlich et al 26 27 adopted an innovative strategy of in situ growth of cobalt oxide (Co 3 O 4 ) nanowires on 3D graphene foam grown by CVD. The graphene/Co 3 O 4 composite was used as a monolithic free-standing supercapacitor electrode and exhibited a high specific capacitance of ∼1100 F g −1 at a current density of 10 A g −1 with excellent cycling stability after 1000 cycles.…”
Section: Introductionmentioning
confidence: 99%